Athletes from Uzbekistan competed on international courts (1950-1980.) (Historical analysis) - Normo‘minov, Azizbek (The Lingua Spectrum, 2025)
This article analyzes the international cooperation of the Uzbek SSR for the development of the sports sphere in the period 1950-1980. During this period, Uzbekistan was part of the Soviet Union, and sports policy was conducted mainly centrally. Uzbek athletes have participated in various international competitions, including Olympic Games, world and European Championships, as part of the Soviet delegation. This article will cover Uzbekistan’s role in the international sports field within the framework of the Soviet system, cooperation with prestigious sports organizations and the impact of this process on the development of the country’s sports infrastructure.